1998
DOI: 10.2176/nmc.38.suppl_152
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler Pattern after Intracarotid Papaverine and Prostaglandin E<sub>1</sub> Incorporated in Lipid Microsphere in Patients with Vasospasm

Abstract: We studied the effects of intracarotid papaverine and prostaglandin E1 incorporated in lipid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the present study, we demonstrated that in principal it is possible to incorporate PGE 2 into (85:15) PLGA microspheres using a new and innovative cosolvent emulsion method. Even if the incorporation and release of another prostaglandin (PGE 1 ) from a lipid microsphere has already been described by Kanamura et al21 for its use in the treatment of vasospasm, to our knowledge the present report demonstrates for the first time the incorporation and controlled release of PGE 2 from PLGA microspheres. There are various experimental studies with different PLGA‐based scaffolds22–24 and microspheres25–31 loaded with signaling molecules and growth factors for different purposes in tissue engineering, as summarized in Table I.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…In the present study, we demonstrated that in principal it is possible to incorporate PGE 2 into (85:15) PLGA microspheres using a new and innovative cosolvent emulsion method. Even if the incorporation and release of another prostaglandin (PGE 1 ) from a lipid microsphere has already been described by Kanamura et al21 for its use in the treatment of vasospasm, to our knowledge the present report demonstrates for the first time the incorporation and controlled release of PGE 2 from PLGA microspheres. There are various experimental studies with different PLGA‐based scaffolds22–24 and microspheres25–31 loaded with signaling molecules and growth factors for different purposes in tissue engineering, as summarized in Table I.…”
Section: Discussionmentioning
confidence: 43%
“… Surface erosion due to hydrolytic degradation [two different PLGA polymers from a previous study (corresponding to our previous results from Ref. 21) after 0, 40, and 80 days]. …”
Section: Resultsmentioning
confidence: 93%
“…Thus, papaverine has been used in conjunction with nimodipine, nicardipine, prostaglandins to enhance it’s safety and efficacy. 150 …”
Section: Clinical Use Of Intracarotid Drugsmentioning
confidence: 99%
“…It is probably unlikely that this receptor is responsible for endocytosis of large liposomes (>50-nm) [2,70]. The 50-nm unilamellar liposomes, containing papaverine and Prostaglandin E, have been shown to augment cerebral blood flow [2,71,72]. A novel method to deliver chemotherapeutic drugs in such a situation is to use immunoliposomes.…”
Section: Specific Transport Mechanismsmentioning
confidence: 99%